IMPLEMENTASI KEBIJAKAN PELAYANAN SURAT IZIN USAHA PERDAGANGAN DI BADAN PELAYANAN PERIZINAN TERPADU KOTA MANADO - DJUKISANA, FRAHMAWATI (Sam Ratulangi University, 2014)
Trading License is a license to be able to carry out trading business. But in reality the policy implementation services business trading license has not run baiktolak of the matter, this study dimasuksudkan to answer the question of how policy implementation services business license trade. In this study using the model of George C. Edwards III where implementation can be started from the abstract state and a question of whether the conditions for policy implementation to be successful is communication, communication is between implementing policies / programs with community target groups. Resources, is the human resources and financial resources available or provided for the implementation of policies / programs. Disposition, is characteristic that attaches to the pelakana like honesty, commitment and democratic attitudes. Bureaucratic structure, the structure of the mechanism is operational procedures and organizational structure implementing policy. This research uses descriptive qualitative approach through in-depth interviews to 10 informants, observation and tracking documents and this research is assisted by an additional instrument in the form of a list of guidelines for interviewing, recording equipment and stationery. The results showed that in general the overall results of the interview on the results of the implementation of service policies Trade Permit the conclusion that the rate of successful implementation of service policies Trading License in Integrated Licensing Service Agency Manado pretty good. Â Keywords: Implementation of Policies, Services Trade Permit.